Cord blood vitamin A and vitamin D levels in relation to physical growth in exclusively breastfed infants aged 0-6 months - Zhao, Wei; Li, Chao; Shen, Wen Zhi; Li, Kai Yun; Cai, Yi Xi; Li, Feng; Fu, Hong; Peng, Bin; Chen, Jie; Li, Ting Yu; Chen, Li (Frontiers in Endocrinology, 2024)
Background Vitamins A and D are essential for the health of pregnant women and infants. Nevertheless, the relationship between umbilical cord blood vitamins A and D levels and the physical growth of exclusively breastfed infants remains uncertain. Objective This cohort study aims to examine the relationship between cord blood vitamins A and D levels and the physical growth of exclusively breastfed infants aged 0–6 months. Methods 140 singleton mother–infant pairs were recruited in total. Questionnaires were used to collect maternal and infant information, and liquid chromatography was utilized to quantify the levels of vitamins A and D in the umbilical cord blood. Anthropometric measurements were conducted at birth, at 3 and 6 months of age, and the weight-for-age z-score (WAZ), length-for-age z-score (LAZ), head circumference-for-age z-score (HAZ), and BMI-for-age z-score (BMIZ) were calculated. Univariate and multivariate linear regression models were used for the analysis. Results The average concentration of vitamins A and D in cord blood was 0.58 ± 0.20 μmol/L and 34.07 ± 13.35 nmol/L, both below the normal range for children. After adjusting for confounding factors, vitamin A levels in cord blood positively correlated with HAZ growth in infants aged 3–6 months (β= 0.75, P < 0.01) while vitamin D levels negatively correlated with LAZ growth (β= −0.01, P = 0.01) and positively correlated with BMIZ growth (β= 0.02, P < 0.01). Conclusion Higher Vitamin A levels at birth promote HAZ growth in infants aged 3–6 months while higher vitamin D levels at birth promote BMIZ growth in infants aged 3–6 months. Clinical trial registration https://register.clinicaltrials.gov, identifier NCT04017286.